Application of Extreme Value Distribution on Temperature Data in South Sulawesi Province - Sri Dewi Anugrawati (Jurnal MSA ( Matematika dan Statistika serta Aplikasinya), 2025)
Climate change in recent years has resulted in extreme changes in temperature in Indonesia, especially in South Sulawesi Province. Extreme temperature changes will affect human and investment activities, energy use, and disaster events. Therefore, this study aims to model the maximum and minimum temperature data in South Sulawesi Province for the last 75 years. The data used came from observations of maximum and minimum temperatures from January 1945 to December 2020 and were analyzed using the Generalized Extrem Value distribution with the maxima block approach and the Generalized Pareto Distribution with the Peak Overtreshold (POT) approach. The results of the analysis show that these two models can be used to model extreme minimum and maximum temperature data in South Sulawesi Province with the right and optimal selection of blocks and thresholds. The results of the calculation of the return level every 5 years in the projection of the next 50 years show an increase in maximum and minimum temperatures which suggests the need to mitigate the risk of temperature change in order to adapt to climate change.